Macadamia hildebrandii) The effects of ureatreatment on tannin content of macadamia seed (Macadamia hildebrandi) - Tandi, Efraim Japin (Buletin Nutrisi dan Makanan Ternak, 2013)
The purpose of this research was to determine the extent of tannin reduction in macadamia seed through urea treatmen. The research using a complete randomized design (CRD) with factorial pattern 3 x 3 consisting of three levels of urea (2, 3 and 4 percents of 800 grams of macadamia seed) and three long hatching treatment (7, 14 and 21 days) and three replication. The result of research based on analysis of variance by SPSS showed that the level of urea and long hatching treatment and the interaction both factors did not influence on tannin content in macadamia seed.Â  However, when the tannin content which were not treated (4,4433 percents) compare with got treatment (0,4088) showed a highly significant difference.